Systematic Review: Paparan Debu Industri sebagai Faktor Risiko Gangguan Pernapasan pada Pekerja - Arini Dwi Rahmadani; Raudhiyah Hasanah Rambe; Fatimah Az Zahra Lubis; Dinda Purnama Sari; Abdurrozzaq Hasibuan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Industrial dust exposure is a hazardous work environment that can potentially cause respiratory problems in workers, particularly in industrial sectors with production activities that generate high levels of dust particles. This study aims to examine the relationship between industrial dust exposure and respiratory problems in workers through a systematic review. The method used was a qualitative descriptive literature study of scientific articles from 2021-2026 obtained through Google Scholar based on inclusion and exclusion criteria, then systematically analyzed. The results of the study indicate that most studies found a significant relationship between dust exposure and respiratory problems, especially in work environments with dust levels exceeding the threshold limit (TLV). Common symptoms include coughing, shortness of breath, phlegm production, and decreased lung function. In addition to dust levels, other factors such as duration of exposure, length of service, smoking habits, and the use of personal protective equipment (PPE) also play a role in increasing the risk. However, several studies showed insignificant results, which are suspected to be influenced by the use of proper PPE and an effective work environment control system. These findings confirm that dust exposure is a significant, multifactorial risk factor, necessitating comprehensive control efforts through a hierarchy of controls, environmental monitoring, and regular health checks to prevent long-term impacts on worker health.